Fantastically funny tricks - Barnhart, Norm. (2014)
"Step-by-step instructions and photos show how to do a variety of fun and entertaining comedy tricks"--Provided by publisher.
Includes bibliographical references (page 32).
Gr 3-5
Keywords: Tricks -- Juvenile literature